2021
DOI: 10.7150/jca.61299
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and arsenic trioxide synergize to trigger Parkin/pink1-dependent mitophagic cell death in human cervical cancer HeLa cells

Abstract: Mitochondria are involved in various biological processes including intracellular homeostasis, proliferation, senescence, and death, and mitochondrial mitophagy is closely related to the development and regression of malignant tumors. Recent studies confirmed that the hypoglycemic drug metformin (Met) exerted various antitumor effects, protected neural cells, and improved immunity, while arsenic trioxide (ATO) is an effective chemotherapeutic agent for the clinical treatment of leukemia and various solid tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…As described previously [ 24 ], cells (treated with ATO at 2.5 μmol/L or 5 μmol/L for 48 h) were fixed with 2.5% glutaraldehyde and 2% paraformaldehyde in 0.1 mol/L phosphate buffer, followed by 1% osmium tetroxide. After dehydration, thin sections were stained with uranyl acetate and lead citrate for observation.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously [ 24 ], cells (treated with ATO at 2.5 μmol/L or 5 μmol/L for 48 h) were fixed with 2.5% glutaraldehyde and 2% paraformaldehyde in 0.1 mol/L phosphate buffer, followed by 1% osmium tetroxide. After dehydration, thin sections were stained with uranyl acetate and lead citrate for observation.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, some studies involving metformin in non-diabetic cancer patients have yielded promising results [34,35]. Although recent studies by our group and others have found that metformin has significant anti-cervical cancer activity, the mechanisms behind this effect remain elusive [36][37][38][39]. To investigate this, we first used the CCK-8 assay to identify whether metformin induced anti-proliferative activities in different cervical cancer cells.…”
Section: Ampk Activation Impedes Cervical Cancer Tumor Growth In Vitr...mentioning
confidence: 99%
“…In addition to the AMPK pathway, several non-AMPK pathways, such as RAS, AKT, and HIF-1a, may contribute to the anti-cancer effect of metformin (25)(26)(27). Moreover, metformin acts directly on mitochondria by reducing mitochondrial respiration and overall energy efficiency (28). To clarify the effect of metformin on the expression of EGFR in patients with T2DM and OSCC, we conducted a study on EGFR in cancer tissues of non-diabetic OSCC patients taking metformin.…”
Section: Discussionmentioning
confidence: 99%